Frame Repacked Method of Wireless Transmission of Ethernet Audio and Video Streaming - LIU Yu-ping (Gong-kuang zidonghua, 2010)
In view of the serious problem of packet loss existed in transmitting audio and video streaming by use of wireless sensor network technology in coal mine underground,an Ethernet data unpacked/packed method based on FPGA was put forward,namely,an Ethernet data frame would be unpacked into several small packets for transmission at the sending end,while these small data packets would be repacked as an Ethernet data frame at the receiving end,and some processing to the lost or damaged data would be done.Finally,frame check sequence(FCS) of the received data frame will be(re-calculated.) The method makes use of the frame which losses part of the data effectively,improves utilization of effective data,and reduces impact on quality of the received audio and video streaming caused by the loss of audio and video stream data.